LncRNA MALAT1 promotes tumor growth and metastasis by targeting miR-124/foxq1 in bladder transitional cell carcinoma (BTCC) - Jiao, Dechao (Am J Cancer Res, 2018)
Mounting evidence shows that the long non-coding RNA MALAT1 plays a pivotal role in tumorigenesis and metastasis, but the functional significance of MALAT1 in bladder transitional cell carcinoma (BTCC) remains unclear. MALAT1 expression was measured in 56 BTCC patients and 2 BTCC cell lines by real-time PCR. The effects of MALAT1 on BTCC cells were investigated by over-expression approaches in vitro and in vivo. Insights of the mechanism of competitive endogenous RNAs (ceRNAs) were validated through bioinformatic analysis and luciferase assay. MALAT1 up-regulation positively correlated with advanced clinical pathological stage and shorter survival of BTCC patients. Furthermore, MALAT1 over-expression promoted proliferation, migration and invasion of BTCC cells in vitro and in vivo. Particularly, MALAT1 may function as a ceRNA to sponge miR-124, thus modulating the derepression of foxq1, miR-124 target gene, in post-transcriptional levels. The positive MALAT1/foxq1 interaction was confirmed by bivariate correlation analysis, and this positive correlation was of great significance in BTCC tumor growth and metastasis, also accompanied by EMT changes. Overall, this ceRNA regulatory network concerning MALAT1 and the positive MALAT1/foxq1 correlation benefit a better understanding of BTCC pathogenesis and promote the feasibility of lncRNA-directed therapy against this disease.